A Study on the Effect of Metabolic Heat Generation on Biological Tissue Freezing - Sonalika Singh; Sushil Kumar (The Scientific World Journal)
The effect of metabolic heat generation on the freezing of biological tissue has been studied. Quasi-steady approximation is used to solve the Pennes bioheat equation in tissues. Temperature profile and motion of freezing interfaces are obtained for different values of metabolic heat generation. It is observed that metabolism has a significant effect on freezing of biological tissues during cryosurgery.